Proficiency Testing to Assess Technical Performance for CTC-Processing and Detection Methods in CANCER-ID. (25th January 2021) - Neves, Rui P L; Ammerlaan, Wim; Andree, Kiki C; Bender, Sebastian; Cayrefourcq, Laure; Driemel, Christiane; Koch, Claudia; Luetke-Eversloh, Merlin Verena; Oulhen, Marianne; Rossi, Elisabetta; Alix-Panabières, Catherine; Betsou, Fay; et al.
Abstract: Background: Multiple technologies are available for detection of circulating tumor cells (CTCs), but standards to evaluate their technical performance are still lacking. This limits the applicability of CTC analysis in clinic routine. Therefore, in the context of the CANCER-ID consortium, we established a platform to assess technical validity of CTC detection methods in a European multi-center setting using non-small cell lung cancer (NSCLC) as a model. Methods: We characterized multiple NSCLC cell lines to define cellular models distinct in their phenotype and molecular characteristics. Standardized tumor-cell-bearing blood samples were prepared at a central laboratory and sent to multiple European laboratories for processing according to standard operating procedures. The data were submitted via an online tool and centrally evaluated. Five CTC-enrichment technologies were tested. Results: We could identify 2 cytokeratin expressing cell lines with distinct levels of EpCAM expression: NCI-H441 (EpCAM high, CK pos ) and NCI-H1563 (EpCAM low, CK pos ). Both spiked tumor cell lines were detected by all technologies except for the CellSearch system that failed to enrich EpCAM low NCI-H1563 cells. Mean recovery rates ranged between 49% and 75% for NCI-H411 and 32% and 76% for NCI-H1563 and significant differences were observed between the tested methods. Conclusions: This multi-national proficiency testing of CTC-enrichment technologies has importance in the establishment of guidelines for clinically applicable (pre)analytical workflows and the definition of minimal performance qualification requirements prior to clinical validation of technologies. It will remain in operation beyond the funding period of CANCER-ID in the context of the European Liquid Biopsy Society (ELBS).